Strategies In Communication Used By English Department Students In Muhammadiyah University Of Surakarta:A Case Study In Saturday English Gathering (SEGA) Program - Sari, Ambar Ratna; , Prof. Dr. Endang Fauziati, M.Hum; , Nur Hidayat, S.Pd., M.Pd (2015)
This research describe about the type, the frequency and the dominant type of communication strategies used by English Department students in Muhammadiyah University of Surakarta in Saturday English Gathering (SEGA) program. Data of the research are taken from students of Saturday English Gathering (SEGA) program. The object of this study is communication strategies used by the fourth semester students when they were speaking English in Saturday English Gathering Muhammadiyah University of Surakarta in 2015 period. The data are the transcript of students' utterances in SEGA. The data are taken by observation, recording and transcribing, note taking, the last validity and reliability. The researcher uses descriptive qualitative research by Celce-Murcia Taxonomy of CS. The result of data analysis the researcher found 4 types with 10 subtypes of communication strategy that used by the students in SEGA program UMS. They were, a) Stalling or Time-gaining Strategies: (1) Self Repetition with 25,38%, (2) Fillers with 41,11%. b) Interactional Strategies: (1) Appeal for Help with 1,52% (Indirect) and 7,1% (Direct), (2) Requests (Repetition) with 1,01%. c) Achievement or Compensatory Strategies: (1) Retrieval with 4,56%, (2) Code switching with 7,61%, (3) Non-Linguistic Means with 2,53%, (4) Word Coinage with 1,01%, (5) Restructuring with 1,52%. And the last d) Self Monitoring Strategies: (1) Self Initiated Repair with 6,59%. The dominant strategy used by the students is Stalling or Time-gaining Strategies with 66,49% and the lowest percentage is Self Monitoring Strategies with 6,59%. From that data, the researcher estimated there was cause why the students often used stalling and time-gaining strategies. It was because this strategy was the most easy to apply than other types of communication strategies. Sometimes, Stalling and time-gaining strategies spontaneously used by the students. The students usually used words "aaa", "emm", as the strategy to got more time to think or reminded their memories when they lost their word. When they spoke with their friends in public places and felt nervous or afraid, they also used stalling and time-gaining strategies.